การพัฒนาแบบฝึกทักษะการคิดสาระพระพุทธศาสนาเพื่อส่งเสริมการคิดอย่างมีวิจารณญาณสำหรับนักเรียนชั้นมัธยมศึกษาปีที่ 3 - จันจิรา มะโนเพ็ญ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The purpose of this study were to Develop Thinking Skills Exercises in Buddhism Strand for Mathayom Suksa 3 Students on the title integration moral principle for life. The target group consisted of 1 directors, 3 experienced teachers, who taught in social studies, and an educational supervisor in The Office Maehongson Primary Education Service Area 1. The instruments consisted of 4 Development of Thinking Skills Exercises in Buddhism Strand to Promote Critical Thinking for Mathayom Suksa 3 Students on the title integration moral principle for life and Development of Thinking Skills Exercises assessment. The data were analyzed by using means and standard deviation. The findings were as follows; Four thinking skills exercises in Buddhism Strand to Promote critical thinking were developed. There were (1) Dukkha, (2) Samudaya, (3) Nirodha, (4) Magga. All the Development of thinking skills exercises in Buddhism Strand to Promote critical thinking were appropriate in highest Level with the means of 2.86 and standard deviation of 0.24.